Snapping: Feminist Pedagogy and Navigating the “New” Right - Latimer, Heather (Atlantis)

(untitled) (Mount Saint Vincent University, 2020)
This paper uses anecdotal and affect theory to think through the repercussions of feminist pedagogy while navigating the “new” right. It extends Sara Ahmed’s metaphors of the feminist snap and the feminist ear as pedagogical and epistemological tactics.